1992
DOI: 10.4141/cjps92-011
|View full text |Cite
|
Sign up to set email alerts
|

The effects of tillage systems and crop rotations on soil water conservation, seedling establishment and crop yield

Abstract: Lafond, G. P., Loeppky, H. andDerksen, D. A. 1992

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
93
3
4

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(109 citation statements)
references
References 18 publications
7
93
3
4
Order By: Relevance
“…In zero-tillage plots, soil disturbance was restricted to the seeding operation. In conventional tillage plots, management included one fall and one spring tillage operation as described by Lafond et al (1992).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In zero-tillage plots, soil disturbance was restricted to the seeding operation. In conventional tillage plots, management included one fall and one spring tillage operation as described by Lafond et al (1992).…”
Section: Methodsmentioning
confidence: 99%
“…The effect of tillage on grain legume yield (Lafond et al 1992) and the influence of including grain legumes in the rotation on the yield of succeeding cereal crops (Bremer et al 1988;Stevenson et al 1995) have been well documented. Little information is available, however, on the effects of tillage and preceding crops on nitrogen (N) fixation by grain legumes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Saskatchewan, the soil moisture content in the 0-60 cm profile was found to be 9% higher in no-till plots than in those under conventional tillage (Lafond et al 1992). Our research from Ririe indicates that shallow subsoiling has the potential to increase soil moisture availability at depths between 61 and 90 cm of the soil profile at anthesis, when precipitation is available to recharge the upper 90 cm.…”
Section: Discussionmentioning
confidence: 87%
“…Hussain et al (1998) the intensity of soil disturbance and tillage frequency increases volumetric soil moisture content decreased. Lafond et al (1992) reported that NT increase the water storage capacity of the soil and increase the available water for crop growth. Maintenance of stubble on the surface enhanced the capacity to store soil water reserves significantly under NT but not under CT.…”
Section: Introductionmentioning
confidence: 99%